Silver-Catalyzed Fluorination Reactions - Xu, Tao; Liu, Guosheng (Synlett, 2012)
The silver-catalyzed fluorination has been developed for introducing a fluorine atom into organic compounds. Recent progress in this area is reviewed with an emphasis on the silver-catalyzed intramolecular aminofluorination of allenes.
Keywords: silver; fluorination; cyclization; allene; fluoropyrrole